Islam and Global Social Justice: Exploring the Teachings of Islamic Civilization in Responding to Modern Economic Inequality - Syifa, Ahmad (Sekolah Tinggi Agama Islam Kuningan, 2025)
Growing global economic inequality has raised concerns over the failure of the conventional economic system to create social justice. In this context, Islamic teachings offer an alternative approach that emphasizes wealth distribution, social solidarity, and moral balance as an integral part of the economic system. This research aims to (1) explore the values of social justice in Islamic civilization; (2) analyze the relevance and implementability of these principles in responding to global economic inequality; and (3) provide recommendations for Islamic-based redistributive policies. This research uses a qualitative approach with a literature study method and thematic analysis of Islamic primary sources as well as academic literature and current global data. The results show that values such as al-'adl, maslahah, and ukhuwwah have a fundamental role in building social justice structures. Instruments such as zakat and waqf have proven effective as sustainable wealth redistribution mechanisms, even when compared to conventional fiscal policies. Furthermore, Islamic teachings are able to provide a normative and practical basis for formulating a more ethical and humane global economic system. This study concludes that the integration of Islamic values in global socio-economic policies can be a significant contribution in efforts to tackle economic inequality in a structural and sustainable manner.